2020
DOI: 10.1109/access.2020.3006499
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Application of Grey Wolf Optimizer-Long Short-Term Memory

Abstract: Long short-term memory (LSTM) is widely applied in both academic and industrial fields. However, there is no reliable criterion on selecting hyperparameters of LSTM. Currently, although some widely used classic methods such as random search and grid search have obtained success to some extent, the problems in local optimum and convergence still exist. In this research, we propose to use grey wolf optimizer (GWO) to search for the hyperparameters of LSTM. Through the method, the superiority of metaheuristic in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Generally, constructing the hybrid ML models is a complex and time-consuming procedure 6,14-18 . However, the hybrid ML models have higher accuracy than the physically-based methods [20][21][22][23] . Therefore, using the hybrid ML models to precisely estimate the ET is a core issue in hydrology and ecology.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Generally, constructing the hybrid ML models is a complex and time-consuming procedure 6,14-18 . However, the hybrid ML models have higher accuracy than the physically-based methods [20][21][22][23] . Therefore, using the hybrid ML models to precisely estimate the ET is a core issue in hydrology and ecology.…”
Section: Discussionmentioning
confidence: 97%
“…overcome the drawbacks of ML models, meta-heuristic algorithms such as flower pollination algorithm (FPA) 6 , firefly algorithm (FFA) 11 , intelligent water drops (IWD) algorithm 12 , whale optimization algorithm (WOA) 18 , grey wolf optimizer algorithm (GWO) 19,20 etc., were employed to determine the optimal hyperparameters of ML models. Studies have shown that ML models coupled with meta-heuristic algorithms have higher computing performance than that of single ML models and physically-based methods 12,16,18,21,22 .…”
mentioning
confidence: 99%
“…In that regard, a GWO is employed to optimize the LSTM hyperparameter and to build an encouraging input data regression model. The application of GWO-based LSTM to predict the degradation trend of the airborne fuel pump is employed in [32]. It is worth mentioning that the performance of deep learning models is data-dependent and tuning the hyperparameter values improves the performance of data prediction.…”
Section: Gwo-lstm For Day-ahead Weather Forecastingmentioning
confidence: 99%
“…In this study, a robust GWO is considered to ensure that the optimal scheduled solution can survive under a certain degree of variability under uncertain conditions in the scheduling problem decision variables and renewable forecasts. The optimization problem given for the deterministic UC-ELD formulation is reformulated by (32) considering an additional constraint that represents the normalized variation of the objective function and then handled by using a barrier function if the robustness threshold is not maintained. min…”
Section: Uncertainty Modelling Through Perturbationmentioning
confidence: 99%
“…In the main loop, the fuel pump pumps the oil from the oil feeding tank to the oil storage tank. For cycling, the oil in the storage tank returns to the feeding tank by gravity through the valve [39]. rough cycling, the working environment of the test pump is stable.…”
Section: Construction Of Airborne Fuel Pump Testbed a Centrifugal Ac ...mentioning
confidence: 99%